Pengaruh Model Pembelajaran Picture And Picture Terhadap Hasil Belajar Matematika Siswa Kelas VI UPTD SD Negeri 124401 Jl. Dahlia Pematang Siantar - Romayeni Purba; Minar Lumbantobing; Esti Marlina Sirait (Journal on Education, 2023)
Good Mathematics learning is in the form of a learning process that can convey effective material. Learning models and media are important components. In this study the research method used is a research method with a quantitative approach. The type of research used by researchers is experimental research, namely the Quasi Experimental Design method. In this research design using experimental research, namely Quasi Experimental Design type Nonequivalent Control Group Design. This research was conducted at UPTD SD Negeri 124401 Jl. Dahlia Pematangsiantar with a sample of 2 classes namely class IV-A and class IV-B, the (experimental) group of the class has 23 students and the (control) group from class IV-A has 28 students, so the total sample is 51 students. The results of the study showed an increase in learning outcomes classically, which can be seen from the average post-test score of the experimental class, namely 81.75. Based on the Paired Samples Test table, it is known that the significance value (2 tailed) is 0.000. Then 0.000 < 0.05. It can be concluded that Ho is rejected and Ha is accepted, which means that there is a significant influence between the Picture and Picture learning model on mathematics learning outcomes in class VI UPTD SD Negeri 124401 Jl. Dahlia Pematangsiantar. The research results show that the Picture and Picture learning model on mathematics learning outcomes in class VI has a positive influence on learning outcomes from conventional learning, namely the average value of the experiment is 81.75, the average value of the control class is 71.76 which indicates that the average value of the posttest the experimental class is superior to the control class. There is a difference in t-count ≥ t-table (10.16 ≥ 2.070. Thus the learning outcomes of students using the Picture and Picture learning model for mathematics learning outcomes in class VI are better than using conventional learning models.